Rare Malignant Indications for Liver Transplantation: A Collaborative Transplant Study Report - Houben, Philipp; Schimmack, Simon; Unterrainer, Christian; Döhler, Bernd; Mehrabi, Arianeb; Süsal, Caner (Frontiers in Surgery, 2021)
Introduction: Hepatocellular carcinoma (HCC) is by far the leading malignant indication for liver transplantation (LT). Few other malignancies, including cholangiocellular carcinoma (CCC), metastases from neuroendocrine tumors (NET), and sarcomas of the liver (LSAR), also are commonly accepted indications for LT; however, there is limited information on their associated LT outcome. Methods: Graft and patient survival in 14,623 LTs performed in patients with HCC, CCC, NET, and LSAR during 1988 – 2017 and reported to the Collaborative Transplant Study were analyzed. Results: 13,862 patients had HCC (94.8%), 498 (3.4%) CCC, 100 (0.7%) NET, and 163 (1.1%) LSAR. CCC patients showed a 5-year graft survival rate of 32.1%, strikingly lower than the 63.2% rate in HCC, 51.6% rate in NET, and 64.5% rate in LSAR patients (P < 0.001 for all versus CCC). Multivariable Cox regression analysis revealed a significantly higher risk of graft loss and death due to cancer during the first five post-transplant years in CCC versus HCC patients (HR 1.77 and 2.56; P < 0.001 for both). The same risks were increased also in NET and LSAR patients, but did not reach statistical significance. Conclusions: Among patients with rare malignant indications for LT, CCC patients showed significantly impaired graft as well as patient survival compared to HCC patients. The observed differences might challenge traditional decision-making processes for LT indication and palliative treatment in specific hepatic malignancies.